Joining technologies for composites and dissimilar materials. Volume 10 : proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Cloud, Gary L.; Patterson, Eann; Backman, David (Springer, 2016)
Joining Technologies for Composites and Dissimilar Materials, Volume 10 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the tenth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Composite Joints Non-Adhesive Bonding Adhesive Bonding Joining of Ceramic & Other Materials.
Keywords: Joints (Engineering) -- Congresses.; elektronické knihy; electronic books